Pengaruh Infotainment Insert TransTV Pada Penyebaran Berita Ghibah Di Komplek Taman Beringin Patra - Anggi Anggi Rahmatunisa; Fifi Hasmawati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "The Influence of Transtv Insert Infotainment on the Dissemination of Backbiting News in the Taman Beringin Patra Complex". The aim of the research is to find out whether TransTV infotainment inserts can spread news of backbiting in the Taman Beringin Patra Complex. This research can be explained that it uses a counting method or is often called a quantitative method. It can be explained that this research was carried out in the field (field research), carrying out an activity where there was a casual approach, meaning this approach was carried out by finding out what the causes and effects were between variables. Researchers did this by taking a sample of 80 respondents or target people who could help with this research, namely the people in the Taman Beringin Patra Complex. This research instrument will be carried out with various test stages, namely using validity and reliability tests. Then the basic assumptions are tested. This research will carry out a stage with data analysis techniques used, namely simple linear regression analysis, t test, and coefficient of determination test. It can be explained that there is an influence of Infotainment Insert on the spread of backbiting news. This can be seen from the results of the t test which shows a significance value of 0.000 < 0.05 and a calculated t value of 4,459 > t table 1,990. And the results of the coefficient of determination test, the R square value is 0.203, which shows that the influence or influence of TransTV infotainment inserts on the spread of backbiting news is 20.3%.